Management of crude oil contamination in the Cúcuta aqueduct (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2007)
On June 2, 2007, at 3:02 a.m., an incident occurred that is currently under investigation, causing the rupture of the Caño Limón - Coveñas oil pipeline owned, managed, and operated by ECOPETROL S.A. at km. 238 in the village of La Don Juana, municipality of Chinácota. This resulted in the spill and subsequent discharge of 9,316 barrels of oil into the Pamplonita River, contaminating the main source of supply for the aqueduct of the capital of the department of Norte de Santander, located in northeastern Colombia. This situation forced the closure of the aqueduct, leaving more than 480,000 inhabitants, equivalent to 70% of the population, without water for more than nine days, an unprecedented event in the history of Colombia. Experts consider it the most significant crude oil spill in Colombian oil history due to the impressive sanitary, environmental, ecological, social, and economic damage it caused.
Keywords: spill; oil pipeline; rationing; environmental damage; sanitary; ecological; Cúcuta; Aguas Kpital Cúcuta S.A.